Application of Learning Strategies and Emotional Intelligence on Learning Outcomes of Music Art Students of Tebing Tinggi Public 2 Senior High School - Ribka Wisudarni S, Venny; Sitompul, Harun; Situmorang, Julaga (KnE Social Sciences, 2023)
This study aims to compare students ’art learning outcomes through the application of accelerated learning strategies with expository learning strategies, emotional relationship intelligence with students’ learning outcomes of music art. This research is an experiment (experiment) and treatment (treatment). The study population was all students of SMA Negeri 2 and 3 Tebing Tinggi. The sample was determined by cluster random sampling technique. This study used a quasi-experimental research method. The results of the study are differences in the learning outcomes of students who learn with accelerated learning strategies both in groups of students who have high emotional intelligence and students who have low emotional intelligence. Higher learning outcomes for students who are taught the art of music with accelerated learning strategies from the expository. The high emotional intelligence learning outcomes taught with accelerated learning strategies were better than students who studied expository learning, while the learning outcomes of students who had low emotional intelligence who were taught with accelerated learning strategies were better than students taught expository learning strategies. These results indicate that the acceleration learning strategy is more effectively applied in students’ learning of the art of music in order to improve learning outcomes of high emotional intelligence. Keywords: expository learning strategies; music art; emotional intelligence